Online Religious Practices in a Second Reality: Constructing Religious Identity in Cyberspace - Wisnu Pudji Pawestri (Journal of Innovative and Creativity, 2026)
Advances in information technology have had a significant impact on society. The ease of access afforded blurs the boundaries of space and time, resulting in the formation of a one-dimensional world within cyberspace. The influence of cyberspace on social life is evident at at least three levels: individual, inter-individual, and group. The institutional systems mentioned above create new social relations and identities built within cyberspace. Interestingly, institutions that typically form within social life are now emerging and taking shape within cyberspace. This article examines how a religious study group constructs a “new world” in cyberspace and its identity. The article examines the social solidarity and social identity that form within the “Muslim Berhijrah” religious study group on the WhatsApp Group (WAG) application, and why the group needs a digital space to disseminate its ideological message. The method used is a descriptive qualitative one, incorporating the theory of simulacra proposed by Jean Baudrillard. The results show that social activities within the Muslimah Berhijrah WAG operate as a simulacra space, where religious information produced in cyberspace is interpreted as a tangible reality. These religious consumption patterns shape a communal identity characterized by attachment to traditional information and solidarity based on ideological similarities. In this process, symbolic power relations are exercised through the role of group administrators who control the flow of information and define the boundaries of what is considered legitimate Islam, thus fostering voluntary compliance among members. However, this study also found subject ambiguity, with some members attempting to verify information through other sources, despite remaining within the digital realm, which is also a simulacra.